Drawing African Diasporic women anthropologists in dialogue: Decolonizing the canon - Johnson, Amanda Walker (Anthropology of consciousness, 2023)
Inspired by the use of naming and portraiture together in the Black artivism–such as that protesting the murders of George Floyd and Breonna Taylor–this paper reflects on the use of portrait drawing as a practice of genealogy. While working on a project to raise the visibility of scholars and their works in the African Diaspora, specifically Francophone women anthropologists, I felt compelled to draw their portraits. Drawing African Diasporic women into dialogue from the archive attends to temporality, vision, and listening, elements centered within anthropological practice, but also implicated in the attachment of the discipline to colonial logics, particularly of allochronism, objectification and silencing. The multisensory, embodied and slow practice of drawing alongside reading scholars' works allows for diasporic time-travel, shifting the gaze, and constructing a decolonizing “listening genre”.